PENDAMPINGAN KELAS IBU HAMIL DALAM MEMBERIKAN MOTIVASI ANC BERKUALITAS, UPAYA PENINGKATAN KESEHATAN IBU DAN JANIN - Yenni Aryaneta; Mariyana; Isramilda (Jurnal Pendekar Nusantara, 2024)
Complications of pregnancy and childbirth as a cause of maternal death can be prevented by carrying out regular antenatal care (ANC) visits. Antenatal care is a comprehensive and quality antenatal service provided to all pregnant women. These services can be provided by doctors, midwives, nurses and other medical personnel who are trained and professional. The Indonesian government has made a policy for an integrated antenatal care program of quality and quantity, namely that antenatal care must implement the "7T" service standard with a minimum visit frequency of 4 times during pregnancy. Antenatal services can also be used to provide information to pregnant women and their families to carry out appropriate treatment and immediately have their pregnancy checked if there are danger signs during pregnancy. Factors that influence the health behavior of pregnant women when visiting ANC are divided into predisposing factors, enabling factors and reinforcing factors. Predisposing factors consist of age, education level, occupation, parity, knowledge and attitudes of pregnant women. Enabling factors include distance from residence, family income, and existing information media facilities. Meanwhile, strengthening factors include husband's support, family support, and attitudes and support from health workers..